2016
DOI: 10.1158/0008-5472.can-15-2973
|View full text |Cite
|
Sign up to set email alerts
|

FAP Promotes Immunosuppression by Cancer-Associated Fibroblasts in the Tumor Microenvironment via STAT3–CCL2 Signaling

Abstract: Cancer-associated fibroblasts (CAF) are components of the tumor microenvironment whose contributions to malignant progression are not fully understood. Here, we show that the fibroblast activation protein (FAP) triggers induction of a CAF subset with an inflammatory phenotype directed by STAT3 activation and inflammation-associated expression signature marked by CCL2 upregulation. Enforcing FAP expression in normal fibroblasts was sufficient to endow them with an inflammatory phenotype similar to FAP þ CAFs. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
411
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(432 citation statements)
references
References 45 publications
21
411
0
Order By: Relevance
“…Preliminary findings from our ongoing studies suggest that disruption of FAP protease inhibits pulmonary metastatic outgrowth and that this inhibition correlates with reduced macrophage infiltration (A. Lo et al, unpublished observations), which may be due to downregulation of CCL2 from FAP-deficient CAFs (12,13). Further studies are required to determine if this mechanism can be extended to PDA metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…Preliminary findings from our ongoing studies suggest that disruption of FAP protease inhibits pulmonary metastatic outgrowth and that this inhibition correlates with reduced macrophage infiltration (A. Lo et al, unpublished observations), which may be due to downregulation of CCL2 from FAP-deficient CAFs (12,13). Further studies are required to determine if this mechanism can be extended to PDA metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…There is now ample evidence that CAF produce a large array of chemokines, including the ones specific for granulocytes, such as CXCL1 (Feig et al, 2013; Orimo and Weinberg, 2006). It has recently been reported that CAF also promote migration of monocytic cells to tumors (Yang et al, 2016), but the direct effect of fibroblasts on neutrophil migration has not been previously demonstrated. In our study, PMN-MDSC recruitment by CAF is consistent with the ability of CAF to produce granulocytic chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Incipient data are showing the role of the AXL in the paracrine feedback loop between cancer and fibroblastic cells with significant effects on resistance to conventional therapies, and likely, immunotherapy [149], paving the way for the design of new therapeutic strategies combining AXL targeting with ICBs. Growing evidence shows that FAP, selectively expressed on CAF subtypes and associated with ECM remodeling, induces tumor-promoting inflammation [150][151][152]. Furthermore, as mentioned before, FAP targeting has been shown to synergize with ICB-based immunotherapy [120,150,152].…”
Section: Tumor-extrinsic Factors Fostering Icb Resistancementioning
confidence: 77%
“…Growing evidence shows that FAP, selectively expressed on CAF subtypes and associated with ECM remodeling, induces tumor-promoting inflammation [150][151][152]. Furthermore, as mentioned before, FAP targeting has been shown to synergize with ICB-based immunotherapy [120,150,152].…”
Section: Tumor-extrinsic Factors Fostering Icb Resistancementioning
confidence: 77%